The Efficacy of Antiviral Medications in Managing Blood Oxygen Levels in Covid-19 Patients Afflicted by Chronic Kidney Conditions - Fendy Prasetyawan; Faisal Akhmal Muslikh; Anis Akhwan Dhafin; Elsa Mahardika Putri; Yuneka Saristiana; Susilo Margining Raharjo (Contemporary Journal of Applied Sciences, 2023)
This research assesses the efficacy and safety of employing antiviral drugs in individuals with COVID-19 and chronic kidney disease. The study results reveal a reduced effectiveness of the drug in enhancing oxygen saturation in patients, as indicated by a p-value of 0.026 for SpO2. Consequently, the administration of antiviral drugs to individuals with chronic kidney disease warrants careful consideration. Moreover, there is a need to pay attention to the safety aspects of antiviral drug utilization, particularly with a p-value of 0.026 for Clcr. It is advisable to refrain from using specific antiviral drugs, such as favipiravir, in COVID-19 patients with chronic kidney conditions. However, contemplating the use of remdesivir at an appropriate dosage may be viable if the patient's glomerular filtration rate (GFR) exceeds 30 ml/minute. The study's conclusion underscores the significance of meticulous and personalized management when employing antiviral drugs in COVID-19 patients with chronic kidney disease. A comprehensive consideration of factors such as effectiveness, safety, and the patient's renal health is imperative to ensure an optimal and tailored treatment approach.